Pregancy of trans masculine people: paradox or reinvention of masculinity - Nascimento, Ricardo; Helmman, Fernando; Zigelli Garcia, Olga Regina (RELIES: Revista del Laboratorio Iberoamericano para el Estudio Sociohistórico de las Sexualidades, 2023)
In recent decades, the population of trans people, also known as the T population, has been increasing every day, making its existence visible and bringing new demands to health professionals, including motherhood and/or biological fatherhood. Without intending to exhaust the theme, this article aims to reflect on the pregnancy of male transgender people, questioning whether this phenomenon is a paradox or a reinvention of masculinity. To reflect on this issue, the authors start from a discussion about the body as a social construction, placing, in sequence, masculinity in focus, and then highlighting the phenomenon of transmasculine pregnancy. They conclude that the pregnancy of trans men is the possibility of fulfilling a personal desire to start a family and that they have the biological capacity and the right to give birth, without this delegitimizing their identity, since they do not cease to be men because of this, on the contrary, are pointing to the multiple possibilities that human diversity embraces. At the end, they point out that reflections on the pregnancy of transmasculine people are important to combat prejudice and discrimination, contributing to structural changes in the social construction made around masculinity, femininity and in the very idea of conception.